(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
The text begins from the perception and reception of the globalist or anti-globalist processes over the past 20 years, which have led to a massive growth of the economic, political, and military power of some new (or re-strengthening of some old) world powers, such as for example Russia, China, Turkey, Iran, India, Brazil and other. Based on the new reality of the world economic, geopolitical and cultural "map", the text gives arguments for the obsolescence of traditional civilization, cultural and general "axiological" conceptual-categorical division to East and West, and all stereotypes, misconceptions and prejudice to that division, placed primaryly by the powerful western media propaganda machine for the past two centuries. The brutal and bloody struggle for the preservation of its own hegemonic and dominant position of the imperial and postcolonial forces (predominantly highly developed capitalist states of the EU and NATO, headed by the United States) and their treatment of all others as a postcolonial "rest of the world" gives the right to all those analysts of a variety of philosophical, scientific and theological provenance, which the West and the Rest phrase consider to be the most accurate conceptual-categorical "reflection" of the new world reality. For truth’s sake, this phrase becomes more evident with and unavoidable in the field of research and activity of such an important science and practice of human existence today - bioethics.